The Implementation of Think Pair Share Strategy in Teaching Speaking at SMPN 3 Matur - Alrevina Tri Azhari; Yulmiati Yulmiati; Rika Afriyanti (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2022)
This study aims to find out how English teachers apply the Think Pair Share Strategy and what difficulties are found when implementing the Think Pair Share Strategy in teaching speaking at SMP N 3 Matur. This study uses a qualitative method. The data collection technique used is purposive sampling. The participant in this study was a teacher who taught in class VII at SMP N 3 Matur. The research instruments used were observation, video recorder, and field notes. Researchers used indicators from Phan and Lan (2021). From the research data, it was found that the implementation of the Think Pair Share strategy was optimal, because the teacher had implemented all the procedures in teaching speaking. Although in implementing this strategy there are some difficulties faced by the teacher including there are students who do not convey or add when their friends share ideas in front of the class, there are students who are just silent, but when approached by the teacher to add he wants to add. In implementing this strategy, not all students can share their ideas in front of the class due to time constraints.